PENGARUH STORE ATMOSPHERE, BRAND AMBASSADOR DAN GREEN MARKETING TERHADAP MINAT BELI KONSUMEN INNISFREE CENTRAL PARK MALL - Subagyo; Ananda Nasyatul (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2020)
This study aims to determine the effect of Store Atmosphere, Brand Ambassadors and Green Marketing on Consumer Purchase Interest at Innisfree Central Park Mall. The method used in this study is a quantitative method and the results of the study are based on respondents' answers using a Likert scale. The population in this study is Innisfree Central Park Mall consumers, the sample in this study amounted to 100. Data analysis methods used in this study are Multiple Linear Regression Test, f Test, t Test and Determinant Coefficient. The results showed that simultaneously (f test) showed that there was a significant influence between the Store Atmosphere (X1), Brand Ambassador (X2) and Green Marketing (X3) variables on Consumer Purchase Interest (Y). partially (Test t) Store Atmosphere does not significantly influence Consumer Purchase Interest and Brand Ambassador has no significant effect on Consumer Purchase Interest, while Green Marketing has a significant effect on Consumer Purchase Interest.